Nutritional compound analysis and morphological characterization of spider plant (Cleome gynandra) - an African indigenous leafy vegetable. (October 2017) - Omondi, Emmanuel O.; Engels, Christof; Nambafu, Godfrey; Schreiner, Monika; Neugart, Susanne; Abukutsa-Onyango, Mary; Winkelmann, Traud
Abstract: Spider plant is among the important indigenous African leafy vegetables having the potential to contribute to food and nutritional security in sub-Saharan Africa. The main objective of this study was to quantify the mineral concentration, to identify and quantify glucosinolates and flavonoids in spider plant and further to characterize spider plant entries using important morphological traits. Thirty spider plant entries from different African countries, comprising of farmers' cultivars, gene bank accessions and advanced lines were grown in a field experiment and harvested for leaves, stems, flowers and siliques at different developmental stages. Five plant types based on the stem and petiole colorations were identified. Significant genotypic differences were shown for all the morphological traits except for 100 seed weight and silique weight. High mineral concentrations in the leaf tissue were observed especially for potassium, calcium, magnesium, phosphorus, iron, manganese and zinc. The aliphatic 3-hydroxypropyl glucosinolate was the main glucosinolate detected in all tissues with the highest concentrations in the reproductive organs. Glycosides of quercetin, kaempferol and isorhamnetin were the main flavonoids. Isorhamnetin glycosides were detected in trace amounts in both, leaves and inflorescences, while quercetin and kaempferol glycosides were the dominant flavonoids in the leaves and inflorescences, respectively. This knowledge of beneficial nutrient contents is an incentive for promoting spider plant consumption for improved human health while the morphological diversity analysis will be important for the further development of the spider plant germplasm. Graphical abstract: Highlights: High concentrations of mineral elements observed among the spider plant entries. Glucosinolate and flavonoid concentrations and profiles vary in different plant organs. The main glucosinolate in the spider plant entries is 3-hydroxypropyl glucosinolate. Flavonoids in spider plant entries are glycosides of quercetin, kaempferol and isorhamnetin Variation within and among entries identified for morphological and agronomic traits.